LEXICAL DIFFERENCES IN GOROM LANGUAGE: A SOCIAL DIALECTOLOGY STUDY - Rumalean, Iwan (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2020)
The present study aims to describe and explain lexical differences in Gorom language on age and professional factors in East Seram Regency, Molucca Province, Indonesia, which employs a social dialectology approach. Data were gathered using the Identity method following the linguistics characteristics identity technique. The instrument used was all 880 basic vocabulary of Gorom language. The sources for this study totaled 24 people. Furthermore, the data analysis was done using a snowball sampling technique. The study indicated that the factor of age and profession in Gorom distinguished social dialects. In the findings, farmer and adult speakers share the same lexical forms. As seen from the age factor, both farmers and adults are about the same age, making them easier to construct mutual understanding. On the other hand, civil servants and children use the same linguistic forms. Children use civil servants' speech as a reference for the kind of prestigious speech; therefore, many Gorom children dream of becoming civil servants. Yet, civil servants and children create some linguistic innovations, such as affixation to roots. It shows solidarity among the community and self-actualization of wide-mannered socialization.